Expression and Localization of Aquaporin 1a in the Sea-Bass (Dicentrarchus labrax) during Ontogeny - Giffard-Mena, Ivone; Boulo, Viviane; Abed, Charline; Cramb, Gordon; Charmantier, Guy (Frontiers in Physiology, 2011)
The successful establishment of a species in a given habitat depends on the ability of each of its developing stages to adapt to the environment. In order to understand this process we have studied the adaptation of a euryhaline fish, the sea-bass Dicentrarchus labrax, to various salinities during its ontogeny. The expression and localization of Aquaporin 1a (AQP1a) mRNA and protein were determined in different osmoregulatory tissues. In larvae, the sites of AQP1a expression are variable and they shift according to age, implying functional changes. In juveniles after metamorphosis (D32-48 post hatch, 15 - 25 mm) and in pre-adults, an increase in AQP1a transcript abundance was noted in the digestive tract, and the AQP1a location was observed in the intestine. In juveniles (D87-100 post hatch, 38 - 48 mm), the transcript levels of AQP1a in the digestive tract and in the kidney were higher in sea water than at lower salinity. These observations, in agreement with existing models, suggest that in sea water-acclimated fish, the imbibed water is absorbed via AQP1a through the digestive tract, particularly the intestine and the rectum. In addition, AQP1a may play a role in water reabsorption in the kidney. These mechanisms compensate dehydratation in sea water, and they contribute to the adaptation of juveniles to salinity changes during sea-lagoon migrations. These results contribute to the interpretation of the adaptation of populations to habitats where salinity varies.